ANALISIS PENGARUH SKALA USAHA, UMUR USAHA, PENDIDIKAN PEMILIK TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO KECIL MENENGAH (UMKM) DI DESA SAORNAULI HATOGUAN KECAMATAN PALIPI KABUPATEN SAMOSIR - Herti Diana Hutapea; Eviana N Sinaga (Journal of Economic and Business, 2022)
This study aims to examine and analyze the effect of business scale, business age and owner's education on the use of accounting information for micro, small and medium enterprises through a quantitative study. Sampling using purposive sampling method amounted to 30 owners of SMEs. The data used in this research is primary data. Data was collected by distributing questionnaires to respondents/owners of MSMEs in Saornauli Hatoguan Village. The analytical method used is multiple linear regression analysis and classical assumption test with SPSS tool. From the results of the tests carried out, the results of the research show that the variables of business scale, business age and owner's education have a significant effect on the use of accounting information in MSMEs. While the variable age of business has no significant effect on the use of accounting information in SMEs